Monitoring Intra-annual Spatiotemporal Changes in Urban Heat Islands in 1449 Cities in China Based on Remote Sensing - Li, Yuanzheng; Wang, Lan; Zhang, Liping; Liu, Min; Zhao, Guosong (Chinese geographical science, 2019)
This study aimed to accurately study the intra-annual spatiotemporal variation in the surface urban heat island intensities (SUHIIs) in 1449 cities in China. First, China was divided into five environmental regions. Then, the SUHIIs were accurately calculated based on the modified definitions of the city extents and their corresponding nearby rural areas. Finally, we explored the spatiotemporal variation of the mean, maximum, and minimum values, and ranges of SUHIIs from several aspects. The results showed that larger annual mean daytime SUHIIs occurred in hot-humid South China and cold-humid northeastern China, and the smallest occurred in arid and semiarid west China. The seasonal order of the SUHIIs was summer > spring > autumn > winter in all the temperate regions except west China. The SUHIIs were obviously larger during the rainy season than the dry season in the tropical region. Nevertheless, significant differences were not observed between the two seasons within the rainy or dry periods. During the daytime, the maximum SUHIIs mostly occurred in summer in each region, while the minimum occurred in winter. A few cold island phenomena existed during the nighttime. The maximum SUHIIs were generally significantly positively correlated with the minimum SUHIIs during the daytime, nighttime and all-day in all environmental regions throughout the year and the four seasons. Moreover, significant correlation scarcely existed between the daytime and nighttime ranges of the SUHIIs. In addition, the daytime SUHIIs were also insignificantly correlated with the nighttime SUHIIs in half of the cases.